An analysis on choices of contraception - Pal, Manidip; Roy, Suman K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Contraception is a matter of choice by the end users. The choice varies time to time. Present study tries to find out which type of contraceptive measure people prefer nowadays. Methods: This is a retrospective observational study conducted at College of Medicine & JNM Hospital, WBUHS, Kalyani, India. The contraceptive performance data of the hospital are collected from the computerised data entry register. The study period was from January 2015 to December 2017. Total number of different contraceptive methods (OCP, condom, IUCD, MTP, tubal ligation etc.) accepted by the people were found out. Data was then analysed in comparison to total number of contraception with each other by student ‘t’ test and chi square test. Results: It is found that condom use is significantly increased from 2015 to 2017 (p<0.00001). OCP use is significantly decreased from 2015 to 2017 (p<0.00001). IUCD insertion significantly increased from 2015 to 2017 (P<0.00001) and tubal ligation significantly decreased from 2015 to 2017 (p<0.00001). Conclusions: Contraception choice preference is shifting towards LARCs (long acting reversible contraceptives).